2019
DOI: 10.1111/anae.14534
|View full text |Cite
|
Sign up to set email alerts
|

The LMA® ProtectorTM in anaesthetised, non‐paralysed patients: a multicentre prospective observational study

Abstract: We evaluated the LMA â Protector TM in 280 ASA physical status 1-3 patients aged 18-75 years by assessing the ease of insertion, insertion time, oropharyngeal leak pressure, ease of gastric tube passage and complications. First-attempt and overall insertion success was 234/280 (84; 95%CI 79-88%) and 274/280 (98; 95-99%). Median (IQR [range]) insertion time was 17 (12-25 [5-44]) s, and manoeuvres to facilitate insertion were required in 56 (50-63)% of patients. Median oropharyngeal leak pressure was 31 (26-36 [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
(35 reference statements)
3
12
2
Order By: Relevance
“…The mean oropharyngeal leak pressure of LMA® Protector™ in our study was 30 cmH 2 O, which was in keeping with the previous ndings on LMA® Protector™ by Zaballos, M., (21) and van Zundert(18). The oropharyngeal leak pressure of 30 cmH 2 O was better than most of the other LMAs that were commonly used in clinical practice and meet the needs of laparoscopic surgeries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mean oropharyngeal leak pressure of LMA® Protector™ in our study was 30 cmH 2 O, which was in keeping with the previous ndings on LMA® Protector™ by Zaballos, M., (21) and van Zundert(18). The oropharyngeal leak pressure of 30 cmH 2 O was better than most of the other LMAs that were commonly used in clinical practice and meet the needs of laparoscopic surgeries.…”
Section: Discussionsupporting
confidence: 93%
“…However, our ndings suggested that attention should be given to gastroesophageal regurgitation especially under head-down positions and adequate suction should be conducted before removal of SADs. The incidence of sore throat (25.86%) observed in our study on the rst day after surgery was relatively higher in comparison with 6% in Zaballos, M.'s study (21) and 23.1% in Sng's study. (13) However, all 75 patients experienced mild symptoms and recovered without any further intervention.…”
Section: Discussioncontrasting
confidence: 61%
“…Air was insufflated into the SGA cuff until the pilot balloon black line was located within the green zone. [ 10 ] After successful ventilation was confirmed on capnography, mechanical ventilation was started. Cuff pressure of the SGA was adjusted using a digital cuff pressure monitor (Shiley Pressure Control, Covidien, Germany) to maintain ≤60 cm H 2 O. SGA devices were replaced by ETTs in the following situations for patient safety if the SGA was not inserted in >3 attempts, persistent oropharyngeal leak with inadequate ventilation (end-tidal CO 2 ≥45 mm Hg during pneumoperitoneum), and/or the stomach was inflated enough to cause visual disturbance under laparoscopic view.…”
Section: Methodsmentioning
confidence: 99%
“…the 'worst that can happen' [53]. Zaballos et al [54] recently conducted a multicentre, prospective, observational study in 280 non-paralysed patients with 'easy' airways. The then newly introduced LMA-Protec-tor® (Teleflex™ Medical Europe, Westmead, Ireland) was inserted blind.…”
Section: Why the Need For Sad Placement Under Direct Vision?mentioning
confidence: 99%